A Comprehensive Review: Molecular and Genealogical Methods for Preserving the Genetic Diversity of Pigs - Vladimir Margeta; Dubravko Škorput; Ivona Djurkin Kušec; Zlata Kralik; Goran Kušec; Kristina Gvozdanović (Applied Sciences)
Anthropogenic activities and rapidly increasing climate change have led to a significant loss of genetic diversity in domestic animals. Genealogical data have traditionally been used to monitor genetic diversity. However, due to dependency on pedigree completeness and significant errors that can occur in genealogical records, inaccurate estimation of population parameters, such as the inbreeding coefficient or effective population size, might occur. To reduce possible errors, it is necessary to combine genealogical data with molecular data. An integrated approach using genealogical and molecular data leads to the optimization of breeding programs while controlling the inbreeding that can occur within the population of domestic animals. Molecular techniques such as single nucleotide polymorphism (SNP) genotyping, whole-genome sequencing (WGS), or genome-wide association studies (GWASs) enable a detailed understanding of breed-specific genetic profiles and their use in conservation programs. In addition, molecular methods such as structural variation (SV) analysis and pangenome and epigenomic profiling provide a more comprehensive insight into genetic diversity. The conservation of genetic diversity is of particular importance for an autochthonous domestic breed due to its resilience to unfavorable climatic conditions, its specific productive traits, and its disease resistance. A combined approach of genealogical and molecular data helps to maintain genetic diversity and sustainable agricultural systems under evolving environmental challenges.